2020
DOI: 10.3389/fchem.2020.00312
|View full text |Cite
|
Sign up to set email alerts
|

A New Family of Jumonji C Domain-Containing KDM Inhibitors Inspired by Natural Product Purpurogallin

Abstract: Aberrant epigenetic modifications are involved in cancer development. Jumonji C domain-containing histone lysine demethylases (KDMs) are found mainly up-regulated in breast, prostate, and colon cancer. Currently, growing interest is focusing on the identification and development of new inhibitors able to block the activity of KDMs and thus reduce tumor progression. KDM4A is known to play a role in several cellular physiological processes, and was recently found overexpressed in a number of pathological states,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…LSD1 is the first identified histone demethylase ( 50 ). HDMs in JHDMs include Fe 2+ - and α-ketoglutarate-dependent hydroxylases, and seven phylogenetically distinct subfamilies were identified in this family ( 51 ).…”
Section: Histone Methylation Modificationmentioning
confidence: 99%
“…LSD1 is the first identified histone demethylase ( 50 ). HDMs in JHDMs include Fe 2+ - and α-ketoglutarate-dependent hydroxylases, and seven phylogenetically distinct subfamilies were identified in this family ( 51 ).…”
Section: Histone Methylation Modificationmentioning
confidence: 99%
“…[6] Representative examples of secondary metabolites belonging to this group are purpurogallin 1, [7,8] theaflavin 2, [9,10] fomentariol 3, [11] aurantricholone 4, [12] goupiolone A 5 [13] and crocipodin 6 [14] (Figure 1). Furthermore, we have showed that properly functionalized benzotropolone 7 act as very potent inhibitors of lysine demethylase JMJD2 A, [15] a subtype of the Jumonji C (JmjC)containing domain family of enzymes, [16][17][18] responsible of the demethylation of N-methylated histone lysine side chains. This epigenetic modification has shown dramatic effects in cell proliferation causing, among other activities, endocrine deregulation and cancer development.…”
mentioning
confidence: 99%
“…[31][32][33] Following our interest in the development of continuous flow synthetic methodologies for the synthesis of biologically active molecules for further characterization of their activity, [34,35] we describe our work in the development of a continuous synthetic procedure for the preparation of benzotropolone core ring present in this family of compounds, and further derivatization to render the recently described epigenetic modulator 7. [15] In order to develop an efficient methodology that eventually allows, not only the isolation of larger quantities of compound 7, [15] but also the preparation of other derivatives in a reproducible manner, we started to study the adequacy of the benzotropolone core ring formation reaction under continuous flow. Besides the different methodologies described in literature for the preparation of benzotropolones, [36][37][38][39] peroxidase-mediated condensation reaction of catechol and pyrogallol derivatives stands out as the most frequently used methodology for the formation of benzotropolone ring, [6,14,15,40] so these reaction conditions were chosen as starting point.…”
mentioning
confidence: 99%
See 2 more Smart Citations